Make pandemics lose their power (2020)
COVID-19 has had the power to do what few other international shocks could have done. It has sickened millions around the world in a matter of months, killed hundreds of thousands, and created a global economic crisis unprecedented in modern times. People around the world have been directed to stay at home for months to avoid catching the disease or contributing to its rapid spread. Massive job losses and economic ruin have occurred globally. Most schools around the world closed for a prolonged period, or they are still out. At least one national leader appears to have died from COVID-19,1 and other national leaders who are either older or have certain underlying medical conditions run the risk of having a severe outcome should they become ill. Travel around the world has diminished to a fraction of what it was. While the disease has unified some countries in their collective effort to pursue a vaccine and to assist lower-income countries, it has deepened international fissures between others. It has underscored the importance and limits of international organizations in this kind of crisis. In the big picture, COVID-19 has shown the extraordinary power of pandemics to do harm. Pandemics are in a small category of events that have destructive power on a global scale, posing risks that have been called global catastrophic risks.